2012
DOI: 10.3402/ejpt.v3i0.18479
|View full text |Cite
|
Sign up to set email alerts
|

The validation of the Polish version of the Posttraumatic Diagnostic Scale and its factor structure

Abstract: BackgroundPosttraumatic Diagnostic Scale (PDS) is a self-descriptive measure developed to provide information regarding posttraumatic stress disorder (PTSD) diagnosis and symptom severity.ObjectivesThe aim of this article is to report on the validation of the Polish version of PDS and to test its factor structure with reference to two models: an original three-factor model (Reexperiencing, Avoidance, and Arousal) and alternative five-factor model (Reexperiencing, Avoidance, Numbing, Dysphoric Arousal, and Anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
3
14
1
Order By: Relevance
“…The initial analysis based on symptoms according to DSM-IV proved that the best model contains 5 factors according to the proposal of . This result is consistent with a previous study that used the PDS by Dragan et al (2012), who achieved a slightly better fit of the 5-factor model than the classical DSM-IV 3-factor model of PTSD symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The initial analysis based on symptoms according to DSM-IV proved that the best model contains 5 factors according to the proposal of . This result is consistent with a previous study that used the PDS by Dragan et al (2012), who achieved a slightly better fit of the 5-factor model than the classical DSM-IV 3-factor model of PTSD symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…They refer to the model of one general factor, three factors, four factors, according to King et al (1998) and Simms et al (2002), and five factors see Table 2; models assumed correlation among latent variables, without higher-order factors). The aim of this analysis was to examine the extent to which the items of PDS-5 referring to the PTSD DSM-IV symptoms retained in DSM-5 were able to reach the same structure of symptoms as other instruments (as well as earlier PDS; Foa, Cashman, Jaycox, & Perry, 1997; see for instance Dragan, Lis-Turlejska, Popiel, Szumiał, & Dragan, 2012).…”
Section: The Pds-5 Structure Of Ptsd According To Dsm-ivmentioning
confidence: 99%
“…The Posttraumatic Diagnostic Scale (PDS; Foa, Cashman, Jaycox, & Perry, 1997; Polish adaptation: Dragan et al, 2012) is a self-report scale that was designed to measure the presence and severity of PTSD symptoms in addition to detecting persons with diagnosable PTSD. The PDS refers to the main diagnostic categories of the DSM-IV, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…It is also worth adding that cross-sectional studies of different populations in Poland have shown high levels of PTSD. For example, 19.7% of university-level students met all PTSD criteria as measured with the PDS in a study reported by Dragan, Lis-Turlejska, Popiel, Szumiał and Dragan (2012). …”
mentioning
confidence: 98%
“…On the whole, the majority of studies indicate that the DSM-IV model does not adequately represent the latent structure of PTSD. Several models have been proposed in the last decades, including two- (Asmundson, Wright, McCreary, & Pedlar, 2003; Buckley, Blanchard, & Hickling, 1998; Taylor, Koch, Kuch, Crockett, & Passey, 1998), three- (Anthony, Lonigan, & Hecht, 1999; Foa et al, 1995), four- (Asmundson et al, 2000; Baschnagel, O'Connor, Colder, & Hawk, 2005; King, Leskin, King, & Weathers, 1998; Simms et al, 2002), and five-factor solutions (Dragan, Lis-Turlejska, Popiel, Szumial, & Dragan, 2012; Elhai et al, 2011; Morina et al, 2010; Watson et al, 1991). Models that have been replicated most consistently across studies are the four-factor models of King et al (1998) and Simms et al (2002), although some researchers argue that both models are in fact mis-specified (Shevlin, McBride, Armour, & Adamson, 2009).…”
mentioning
confidence: 99%